Effects of inbound marketing communications on HEIs' brand equity: the mediating role of the student's decision-making process. An exploratory research. Issue 2 (2nd July 2016) - Royo-Vela, Marcelo; Hünermund, Ute
ABSTRACT: A context of increased competition between higher education institutions (HEIs) for attracting potential national and international students has led universities to implement marketing communication strategies. Those strategies which are used to some extent include, among others, interactive inbound marketing. The purpose of the present exploratory study is to identify how HEIs can develop to improve their image and awareness by using new interactive marketing communication tools mediated by the student's decision-making process. To conduct our investigation, we used both a qualitative (seven semi-structured interviews) and a quantitative survey ( n  = 121) methodology. Based on data analysis, we found that among the areas investigated, interactive marketing communication tools have a great impact on postgraduate students' decision-making process with a corresponding change of perception of the university and attitudes towards the brand. Therefore, even unknown universities with a limited budget can increase their brand awareness and brand image for prospective and current students by using such tools.